Innovation input and innovation output: differences among sectors - Lesley Potters (European Commission, Joint Research Centre (JRC), 2009)
This research investigates deals with the impact of various innovation activities on innovation output by using Spanish CIS3 data on 3,247 innovative firms and applying several Knowledge Production Functions. It is confirmed that different innovation activities lead to differences in both the propensity to innovate and innovation output, depending on the technological characteristics a firm has. In general, internal R&D leads to product innovation, while machinery acquisition leads to process innovation. Size, group belonging and protection of innovations are important determinants for innovation output, but show either a positive or negative relation, depending again on the firm's innovation strategy.
Keywords: O33; 330; R&D; innovation; Knowledge Production Function; double sample selection